Analisis of Total Oil Content and Planktonic Diatom (Bacillariophyceae) in the Waters of Lalang Strait, Mengkapan Village Siak Regency - Sinaga, Octavia Lorensa Br; Siregar, Sofyan Husein; Nedi, Syahril (Faculty of Fisheries and Marine, Universitas Riau, 2022)
Oil pollution in the waters is one of the factors that affect the abundance of fhytoplankton, especially the diatom. The waters of Lalang Strait, Mengkapan Village, are used as international shipping lanes and industrial areas. This study aims to analyze the total oil content, calculate the abundance of planktonic diatoms, and explain the relationship between the total oil content and the abundance of planktonic diatoms carried out in the Lalang Strait waters, Mengkapan Village, Siak Regency, Riau Province. This research uses survey method. Station 1 is near Tanjung Buton Port, station 2 is in the mangrove ecotourism area, and station 3 is in the fishing port and near the settlement. The result of oil content analysis obtained an average value of 0,00016 ppm. The highest oil content at station 3 is 0,00035 ppm and the lowest at station 2 is 0,00011 ppm. The results of the calculation of the abundance of planktonic diatoms ranged from 5.014 to 22.062 cells/L. The highest abundance at station 1 was 17.716 cells/L. The lowest abundance was at station 2 which was 9.694 cells/L. Simple linear regression test result, obtained equation Y= 14,2644+(-3802,27x). The coefficient of determination (R2)= 0,002 states 0,2 % of the abundance of planktonic diatoms is influenced by oil content and the rest is influenced by other environmental factors. Correlation coefficient (r) = 0,053, so the relationship of total oil content with the abundance of planktonic diatoms is very weak.